Determination of surface water quality based on macrozoobenthos biodiversity and the prevalence of trematodes cercariae in freshwater molluscs - Siti Muyasaroh,; Muntalif, Barti Setiani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Lake Cisanti is the upstream of Citarum River and silting has occurred in the inlet areas. This water body was selected as the research area due to its crucial role for people living in West Java Province despite some pollution issues recently. The research was conducted from January to May 2016 during rainy season. The aim of it was to assess water quality of Lake Cisanti and reveal that Trematodes cearcariae could be used as bio indicator of organic pollution. From identification results, there were 31 morphospecies of macrozoobenthos from seven classes found in Lake Cisanti. Melanoides tuberculata had the highest total density (188 ind/m2). It implied that organic matter due to open defecation polluted Lake Cisanti. Based on the value of CCMEWQI, H’, and FBI, it can be concluded that water quality of Lake Cisanti comprehensively was unpolluted during January-May 2016. Water conductivity and organic carbon of sediment had the strongest correlation with macrozoobenthos biodiversity in Lake Cisanti. In order to comprehensively understand the main factors of physical and chemical parameters of water and sediment parameters influencing macrozoobenthos biodiversity, Principal Component Analysis (PCA) was required. Based on PCA results, there were two main factors of water parameters, F1 (consist of turbidity and COD) and F2 (consist of temperature and conductivity). Those could explain 73.268% variance of all water parameters. Furthermore, the overall prevalence of Trematode cercariae in Molluscs was about 5.49%. There was significant and strong correlation between prevalence of Trematodes cercariae and fecal coliform concentration based on Spearman correlation analysis. It implied that Trematodes cercariae could be considered as a bio indicator of organic pollution, even though a further research is needed to test it in various aquatic ecosystems, both laboratory (man-made ecosystem) and natural ecosystem scales.